Pemberian Psikoedukasi Dampak Cyberbullying Terhadap Kesehatan Mental Pada Siswa - Oktariani; Mirawati; Arbana Syamantha; Rodia Afriza (Yayasan Literasi Sains Indonesia, 2022)
Cyberbullying presents a serious challenge to social life that must receive attention in the digital world. This is a frightening event for everyone, especially for teenagers causing depression, low self-esteem, not being able to concentrate in class, declining academic grades, anxiety and even suicide. Seeing the magnitude of the danger caused by the incident, it is necessary to continue to develop efforts to provide awareness to the public, especially social media users, to use it properly and wisely and to anticipate all things that can harm and hurt others. Spreading hate, threats and anger on social media is an act of violence that has wide and serious implications. Cyberbullying perpetrators often feel superior and justify their behavior towards the victim. Through this activity, it is hoped that students can obtain information about cyberbulling so that in the future it is hoped that these students will no longer bully through social media and be wiser in using social media.